Descriptive analysis of black walnut cultivars and relationship between consumer acceptance and descriptive analysis of black walnuts in a sugar cookie base - Miller, Ashley E. (Kansas State University, 2012)
Researchers evaluated the flavor characteristics of seven black walnut (Juglans nigra L.) cultivars: Brown Nugget, Davidson, Emma K, Football, Sparks 127, Sparrow, and Tomboy using descriptive sensory analysis. Seven trained panelists developed a lexicon for the black walnuts and scored the intensities of the samples for 22 flavor and taste attributes. Results showed that the 7 samples differed significantly (P ≤ 0.05) on 13 of the attributes. For the majority of the attributes, only Emma K differed from the rest of the cultivars by being characterized with lower scores for black walnut ID, overall nutty, nutty-grain-like, nutty-buttery, floral/fruity, oily, and overall sweet. It also was higher in acrid, burnt, fruity-dark, musty/earthy, rancid, and bitter attributes. Researchers then incorporated the black walnut cultivars into a simple cookie recipe and evaluated the samples for differences in flavor attributes using the same trained panelists. Nine of the 25 attributes differed significantly across cultivars: black walnut ID, overall nutty, nutty-buttery, brown, toasted, acrid, rancid, overall sweet, and sweet (P ≤ 0.05). Lower mean scores in black walnut ID, overall nutty, and sweet and higher mean scores in rancid and acrid characterized the Emma K cookie. A PCA biplot revealed that cookies with Football, Sparks 127, and Sparrow walnuts related with one another and the attributes nutty-woody, leavening, and piney. A consumer acceptance test for six of the cookies (Tomboy cultivar was excluded) was also performed. There were four significant clusters of consumers that differed in their acceptance of the cookie samples. Cluster 1 preferred Football, clusters 2 and 3 each showed no overall preference, and cluster 4 preferred Emma K suggesting a set of niche consumers for black walnut cookies. Results presented in this paper can assist black walnut growers in determining which cultivars to plant and harvest. By knowing which cultivars have the most desirable flavor characteristics, growers can focus time and resources on select cultivars, therefore resulting in higher quality black walnuts as products to be sold to consumers in various formats. By consciously choosing which cultivars to harvest, black walnut growers can meet market demand and increase profit.
Keywords: Sensory; Descriptive analysis; Black walnut; Consumer acceptance; Food Science (0359)